Column studies on the adsorption of Cd2+ onto chitosan-coated bentonite - Cenia, Marie Chela B. (2012)
Chitosan-coated bentonite (CCB) was examined for the adsorption of cadmium (II) ions in a fixed bed column. Metal uptake value of 34.44 mg Cd2+/g CCB was obtained at a flow rate of 1 mL/min, 4 cm bed depth and 400 ppm initial concentration. The effect of flow rate bed depth and initial concentration were investigated. Increasing the flow rate resulted in decreased metal uptake, decreased removal efficiency and lower breakthrough time. When bed depth was increased, the metal uptake, the removal efficiency and breakthrough time increased as well. When initial concentration was increased, the metal uptake increased while removal efficiency and breakthrough time decreased. The Thomas and Yoon-Nelson models were tested to fit the experimental breakthrough curves. R2 for both models were in the range of 0.9452-0.9905, however, Yoon-Nelson was found to be a better fit with lower error of estimates.